2005
DOI: 10.1007/s00066-005-1406-7
|View full text |Cite
|
Sign up to set email alerts
|

Effektivität und Toxizität einer Re-Bestrahlung (Re-RT) bei metastatisch bedingter Rückenmarkkompression (MBRK)

Abstract: Re-RT is an effective treatment for an in-field recurrence of MSCC. After a cumulative EQD2 < or = 50 Gy, radiation myelopathy appears unlikely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In our previous studies of spinal Re-RT, we found a cumulative BED 100 Gy 2 to be the safe limit because of the smaller number of patients who received a cumulative BED >100 Gy 2 in those series. 13,14 The safety of a cumulative BED 120 Gy 2 is in accord with the review by Nieder et al, who presented 78 patients who had received spinal Re-RT for different reasons (not MSCC alone). 5 Nieder and colleagues found no case of radiation myelopathy when the cumulative BED did not exceed 120 Gy 2 , the BED of each RT (first course of RT plus Re-RT) did not exceed 98 Gy 2 , and when the interval between first course of RT and Re-RT was at least 6 months.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In our previous studies of spinal Re-RT, we found a cumulative BED 100 Gy 2 to be the safe limit because of the smaller number of patients who received a cumulative BED >100 Gy 2 in those series. 13,14 The safety of a cumulative BED 120 Gy 2 is in accord with the review by Nieder et al, who presented 78 patients who had received spinal Re-RT for different reasons (not MSCC alone). 5 Nieder and colleagues found no case of radiation myelopathy when the cumulative BED did not exceed 120 Gy 2 , the BED of each RT (first course of RT plus Re-RT) did not exceed 98 Gy 2 , and when the interval between first course of RT and Re-RT was at least 6 months.…”
Section: Discussionsupporting
confidence: 60%
“…The Re-RT schedule had no significant impact on motor function, which has been previously reported for both first course of RT and Re-RT of MSCC. [12][13][14][27][28][29] Therefore, in accord with data for the first course of RT, one may consider single-fraction RT or multifraction short-course RT for patients with a poor estimated survival, who will probably not benefit from longer-course RT in terms of better recalcification and local control. 1,30 Survival after Re-RT may be predicted with the help of the prognostic factors identified in this series.…”
Section: Discussionmentioning
confidence: 99%
“…Various neuro-oncologic diseases such as metastatic spinal cord compression (MSCC), cerebral metastases, and brain tumors may lead to neurologic deficits [5,14,18,19]. Twenty to 40% of cancer patients develop metastases within the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Local radiotherapy is indicated postoperatively to achieve local tumor control [21,36,46,47,50] and should be initiated as soon as possible (LoE IIa, grade of recommendation A).…”
Section: Radiotherapymentioning
confidence: 99%